Jagged-1 is induced by mTOR inhibitors in renal cancer cells through an Akt/ALK5/Smad4-dependent mechanism - David Danielpour; Sarah Corum; Patrick Leahy; Anusha Bangalore (Elsevier, 2022)
The mammalian target of rapamycin (mTOR) plays an important role in the aggressiveness and therapeutic resistance of many cancers. Targeting mTOR continues to be under clinical investigation for cancer therapy. Despite the notable clinical success of mTOR inhibitors in extending the overall survival of patients with certain malignancies including metastatic renal cell carcinomas (RCCs), the overall impact of mTOR inhibitors on cancers has been generally disappointing and attributed to various compensatory responses. Here we provide the first report that expression of the Notch ligand Jagged-1 (JAG1), which is associated with aggressiveness of RCCs, is induced by several inhibitors of mTOR (rapamycin (Rap), BEZ235, KU-0063794) in human clear cell RCC (ccRCC) cells. Using both molecular and chemical inhibitors of PI3K, Akt, and TGF-β signaling, we provide evidence that the induction of JAG1 expression by mTOR inhibitors in ccRCC cells depends on the activation of Akt and occurs through an ALK5 kinase/Smad4-dependent mechanism. Furthermore, we show that mTOR inhibitors activate Notch1 and induce the expression of drivers of epithelial-mesenchymal transition, notably Hic-5 and Slug. Silencing JAG1 with selective shRNAs blocked the ability of KU-0063794 and Rap to induce Hic-5 in ccRCC cells. Moreover, Rap enhanced TGF-β-induced expression of Hic-5 and Slug, both of which were repressed in JAG1-silenced ccRCC cells. Silencing JAG1 selectively decreased the motility of ccRCC cells treated with Rap or TGF-β1. Moreover, inhibition of Notch signaling with γ-secretase inhibitors enhanced or permitted mTOR inhibitors to suppress the motility of ccRCC cells. We suggest targeting JAG1 may enhance therapeutic responses to mTOR inhibitors in ccRCCs.